Analysis of Readiness to Apply Etle (Electronic Traffic Law Enforcement) Traffic Unit of Wajo Police in Wajo Regency - Sitti Aminah; Syamsiar Syamsiar; Fajri Fajri (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
With the inauguration of ETLE, it is expected to minimize extortion by officers and improve driving discipline. This study aims to determine and analyze the readiness of the Wajo Police Traffic Unit and describe the supporting and inhibiting factors in the implementation of ETLE (Electronic Traffic Law Enforcement) by the Wajo Police Traffic Unit in Wajo District. This type of research is a qualitative method with a descriptive approach using data collection techniques through observation, in-depth interviews and documentation. The results showed that (i) the readiness of the Wajo Police Traffic Unit in the Implementation of ETLE (Electronic Traffic Law Enforcement) in Wajo Regency was analyzed using the theory of readiness indicators or e-readiness according to Richardus Eko Indrajit (2015: 39), namely: (a) Infrastructure Telecommunication has been carefully planned by the Wajo Regency Government and Wajo Police in accordance with the standards imposed by the National Police (b) The level of connectivity and use of ICT is good enough (c) The capacity of the Wajo Police Traffic Unit is sufficient to control the use of ETLE in Wajo Regency ; (d) the availability of funds and budget for the development of telecommunications infrastructure for the implementation of ETLE in Wajo Regency is still waiting for regulations from the regional government and the National Police; (e) The legal instruments for the implementation of ETLE in Wajo Regency are Law Number 22 of 2009 and Government Regulation Number 80 of 2012; (f) Police is not law is a new paradigm (ii) Supporting and inhibiting factors for the implementation of ETLE (Electronic Traffic Law Enforcement) by the Traffic Unit of the Wajo Police in Wajo Regency (a) Supporting factors include human resources of the Wajo Police Traffic Unit, legal instruments; (b) Inhibiting factors include, among others, facilities and infrastructure, funds/budget, and data on road users' vehicles .